Protein nanopatterns by oxime bond formation - Christman, Karen L (Langmuir : the ACS journal of surfaces and colloids, 2011)
Patterning proteins on the nanoscale is important for applications in biology and medicine. As feature sizes are reduced, it is critical that immobilization strategies provide site-specific attachment of the biomolecules. In this study, oxime chemistry was exploited to conjugate proteins onto nanometer-sized features. Poly(Boc-aminooxy tetra(ethylene glycol) methacrylate) was synthesized by free radical polymerization. The polymer was patterned onto silicon wafers using an electron beam writer. Trifluoroacetic acid removal of the Boc groups provided the desired aminooxy functionality. In this manner, patterns of concentric squares and contiguous bowtie shapes were fabricated with 150-170-nm wide features. Ubiquitin modified at the N-terminus with an α-ketoamide group and N(ε)-levulinyl lysine-modified bovine serum albumin were subsequently conjugated to the polymer nanopatterns. Protein immobilization was confirmed by fluorescence microscopy. Control studies on protected surfaces and using proteins presaturated with O-methoxyamine indicated that attachment occurred via oxime bond formation